Recognition of Aerodynamic Objects on Spectral Portraits Taking into Account Design Features of Turbojets - E. V. Zaiko; P. N. Shumsky (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2023)
In the article the device of radar-tracking recognition allowing on the basis of the analysis of a design of impellent installation to define a class (type) of observable air object is considered. Determination of the class (type) of the observed object was carried out by studying the ratios of the modulation frequencies of the spectral radar portrait. The solving rule, as well as the device block diagram are obtained, allowing to define the class and, in addition, the type of the observed air object equipped with a turbojet engine. To form a posteriori probability density, the numerical method of Monte-Carlo was used. The results of the mathematical modelling, confirming the efficiency of the proposed device, are presented.